2016
DOI: 10.1016/j.nbd.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

MECP2 impairs neuronal structure by regulating KIBRA

Abstract: Using a Drosophila model of MECP2 gain-of-function, we identified memory associated KIBRA as a target of MECP2 in regulating dendritic growth. We found that expression of human MECP2 increased kibra expression in Drosophila, and targeted RNAi knockdown of kibra in identified neurons fully rescued dendritic defects as induced by MECP2 gain-of-function. Validation in mouse confirmed that Kibra is similarly regulated by Mecp2 in a mammalian system. We found that Mecp2 gain-of-function in cultured mouse cortical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…MN5 is well suited for analyzing genetic interactions and cellular consequences of MECP2 gain-of-function alleles because it is (i) individually identifiable, (ii) displays a stereotyped and well quantified morphology [ 48 ], (iii) is physiologically well described [ 49 52 ], and (iv) can be addressed by targeted genetic manipulation [ 18 , 19 , 53 , 54 ] with the binary GAL4-UAS expression system [ 55 ]. We use the C380-Gal4; Cha-Gal80 driver line to heterologously express human MECP2 in MN5 labeled with GFP [ 18 , 19 , 48 , 49 , 53 , 54 ]. C380-GAL4 expresses in about 30 neurons per hemisegment of the Drosophila ventral nerve cord (VNC), most of which are glutamatergic motoneurons including MN5 ( Fig 1b ) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MN5 is well suited for analyzing genetic interactions and cellular consequences of MECP2 gain-of-function alleles because it is (i) individually identifiable, (ii) displays a stereotyped and well quantified morphology [ 48 ], (iii) is physiologically well described [ 49 52 ], and (iv) can be addressed by targeted genetic manipulation [ 18 , 19 , 53 , 54 ] with the binary GAL4-UAS expression system [ 55 ]. We use the C380-Gal4; Cha-Gal80 driver line to heterologously express human MECP2 in MN5 labeled with GFP [ 18 , 19 , 48 , 49 , 53 , 54 ]. C380-GAL4 expresses in about 30 neurons per hemisegment of the Drosophila ventral nerve cord (VNC), most of which are glutamatergic motoneurons including MN5 ( Fig 1b ) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the cellular level, MeCP2 mis-regulation negatively impacts dendritic structure as shown in patients [ 12 ], in vivo in mouse [ 13 16 ], Xenopus [ 17 ], and Drosophila [ 18 , 19 ] models, as well as in primary neuron and slice cultures [ 20 , 21 ]. Additionally, overexpression of MECP2 , specifically the E2 isoform, contributes to apoptosis in cultured neurons [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wwc1 is known to be involved in memory formation, synaptic plasticity, and neuronal morphology. It has also been reported that too much or too little expression of Wwc1 affects neuronal morphology or synapse formation [ 54 , 55 , 56 ]. We hypothesized that de novo methylation of the Wwc1 hyperDMR is important for activity-induced synaptogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…MeCP2 gain of function is associated with MeCP2 duplication syndrome (MDS), which causes severe mental retardation, stunted motor development, early-onset hypotonia, epileptic seizures, and progressive spasticity [ 81 ], and interestingly is also associated with mood alterations such as anxiety, depression, and an autistic-like phenotype [ 82 ]. In contrast to MeCP2 loss-of-function models, MeCP2 gain-of-function models show rescue of dendritic defects [ 83 ] and display augmented paired-pulse facilitation [ 84 , 85 ] indicative of a tight relationship between MeCP2 and synaptic plasticity. Most recent studies have shown that an aberrant increase in the formation and stabilization of dendritic spines occurs in the cerebral cortex of the mouse model of MECP2-duplication syndrome and seems to be mediated by hyperactivation of the ERK pathway [ 86 , 87 ], a major regulator of clustered spine stabilization [ 88 ].…”
Section: Mecp2 and Synaptic Plasticitymentioning
confidence: 99%